Respuesta :

ali015
So you have:
[tex] \frac{3}{x} + 2 = \frac{2}{x} - 1 [/tex]

1) Start off by multiplying both sides by x to simplify the problem:
[tex]\frac{3}{x} + 2 = \frac{2}{x} - 1 \\ x(\frac{3}{x} + 2) = (\frac{2}{x} - 1)x\\ 3 + 2x = 2 - x [/tex]

2) Now isolate the x by moving all terms with x onto one side and all other terms onto the other side:
[tex]3 + 2x = 2 - x\\ 3x = -1[/tex]

3) Finally, divide by 3 on both sides to find the value of x:
[tex]3x = -1\\ x = \frac{-1}{3} [/tex]

------

Answer: x = [tex]\frac{-1}{3}[/tex]